Radiocarbon Dating at Groningen: New and Updated Chemical Pretreatment Procedures. Issue 1 (9th February 2020) - Dee, M W; Palstra, S W L; Aerts-Bijma, A Th; Bleeker, M O; de Bruijn, S; Ghebru, F; Jansen, H G; Kuitems, M; Paul, D; Richie, R R; Spriensma, J J; Scifo, A; et al.
ABSTRACT: The Centre for Isotope Research (CIO) at the University of Groningen has operated a radiocarbon ( 14 C) dating laboratory for almost 70 years. In 2017, the CIO received a major upgrade, which involved the relocation of the laboratory to new purpose-built premises, and the installation of a MICADAS accelerator mass spectrometer. This period of transition provides an opportunity to update the laboratory's routine procedures. This article addresses all of the processes and quality checks the CIO has in place for registering, tracking and pretreating samples for radiocarbon dating. Complementary updates relating to radioisotope measurement and uncertainty propagation will be provided in other forthcoming publications. Here, the intention is to relay all the practical information regarding the chemical preparation of samples, and to provide a concise explanation as to why each step is deemed necessary.